Cancer risks in Lynch syndrome, Lynch-like syndrome, and familial colorectal cancer type X: a prospective cohort study - Bucksch, Karolin; Zachariae, Silke; Aretz, Stefan; Büttner, Reinhard; Holinski-Feder, Elke; Holzapfel, Stefanie; Hüneburg, Robert; Kloor, Matthias; Knebel Doeberitz, Magnus von; Morak, Monika; Möslein, Gabriela; Nattermann, Jacob; et al. (BMC cancer, 2020)
Individuals with pathogenic germline variants in DNA mismatch repair (MMR) genes are at increased risk of developing colorectal, endometrial and other cancers (Lynch syndrome, LS). While previous studies have extensively described cancer risks in LS, cancer risks in individuals from families without detectable MMR gene defects despite MMR deficiency (Lynch-like syndrome, LLS), and in individuals from families fulfilling the Amsterdam-II criteria without any signs of MMR deficiency (familial colorectal cancer type X, FCCX) are less well studied. The aim of this prospective study was to characterise the risk for different cancer types in LS, LLS, and FCCX, and to compare these with the cancer risks in the general population.
Gesehen am 01.04.2021